The cooperation between enterprises: significant part of the innovation process – a case study of the czech machinery industry - Stejskal, Jan; Merickova, Beata Mikusova; Prokop, Viktor (Technická univerzita v Liberci, 2016)
In recent years, we have been able to see the growing importance of knowledge in the context of the emerging knowledge-based global economy. It is commonly accepted that (i) innovations are brought forward through an interactive process of knowledge generation, diffusion, and application; (ii) innovations are increasingly seen as fundamental to the competitiveness of enterprises and economies; and (iii) knowledge is critical to the process of innovation. The relative importance of cooperation on innovative activity varies and depends upon a number of factors, i.e. the number of cooperative ties and the context in which network relations exist. The determinants of R&D cooperation differ depending on the types of cooperation: (i) the positive impact of enterprise size, R&D intensity, and incoming source-specific spillovers is weaker for competitor cooperation, reflecting greater concerns about appropriability and (ii) institutional spillovers are more generic in nature and positively impact all types of cooperation. The question is the effectiveness of different types and subjects of cooperation. This article aims to analyze the impact of (i) the cooperation and participation in the group of enterprises; (ii) cooperation with universities; (iii) the provision of state aid; on overall enterprises' performance. Analysis was performed on data from Community Innovation Survey (CIS) carried out in the Czech Republic between the period 2010-2012 by using own multiple linear regression models. The results confirm the importance of cooperation between enterprises and the positive impact of participation of enterprises in the enterprise groups. Cooperation with universities and research organizations also has a positive impact on the performance of enterprises in the machinery industry in the Czech Republic. We also show that there were inefficient provisions of public aid in machinery industry in the Czech Republic.
Spolupráce mezi podniky: důležitá část inovačního procesu - případová studie českého strojního průmyslu
Keywords: Cooperation; innovation; knowledge transfer; machinery industry; Spolupráce; mezi; podniky; důležitá; část; inovačního; procesu; případová; studie; českého; strojního; průmyslu